Import Substitution of Combination Wire Rope-Part V Specifications for Combination Wire Rope for Fishing Purposes - B., Meenakumari; P.A., Panicker (Fishery Technology, 2025)
Specifications for the manufacture of combination wire rope of 14 separate sizes ranging between 12 and 26 mm dia with six distinct strand constructions each of independent wire rope core (IWRC) and fibre core, using steel wires of three different tensile designations and polypropylene twisted tape covering, are reported in this communication in a format suitable for adoption as standards and as an aid to import substitution of combination wire rope for fishing purposes.